Critique of Galicia’s Sentimental Identity: Sentimentality, History and Reason in Daniel Cortezón - Sanjurjo Díaz, Santiago (Madrygal. Revista de Estudios Gallegos, 2015)
This article offers a first contribution to the philosophical and political criticism surrounding the sentimental idea of Galicia in the essays of Daniel Cortezón (1927-2009). Using Helena Miguélez-Carballeira’s analysis in Galicia, a Sentimental Nation (2013) as a starting point, the investigation explores notions of sentimentality, history and reason in Cortezón’s key theoretical writing, including several unedited texts.